Estetika dan makna motif anyaman ugam (tikar) masyarakat lun bawang - Bell Suut; Ismail Ibrahim; Zaimie Sahibil (Pejabat Karang Mengarang (UPSI Press), 2022)
Mats “Ugam” weaving is one of the oldest traditional crafts of the Lun Bawang which was inherited from their ancestors until today. There are various types of mats by the Lun Bawang, which are name after the materials used. There are sier mats, bebelit mats, layun mats, bulu mats, and rattan mats. Mats have different functions among the Lun Bawang. This research is focusing on the motifs and patterns which was found on the mats which was an added values making it more attractive and colorful. This research was carried out in Lawas, Sarawak. This research was done through field research. Data collection methods was through observations, interviews and book reviews. This research was carried out based on Panofsky theory (1939). This theory is common in analyzing art objects. This research identifies the aesthetics and meaning of motifs. Based on the research they are 9 types of motif found on the Lun Bawang mats. The motifs were inspired from the environments, geometrical shape and manmade objects. The aesthetic of the motif was analyses through elements of art, principle and its structures. Most motifs were arranged translation, symmetrically, varieties and harmony. The motifs have different meaning which can be relate to animisms belief, cultures and daily activities of the Lun Bawang.